Demo: Simulation-as-a-Service to Benchmark Opportunistic Networks - Dede, Jens; Udugama, Asanga; Förster, Anna (Electronic Communications of the EASST, 2021)
Repeatability, reproducibility, and replicability are essential aspects of experimental and simulation-driven research. Use of benchmarks in such evaluations further as sists corroborative performance evaluations. In this work, we present a demonstrator of a simulation service, called ”OPS on the bench” which tackles these challenges in performance evaluations of opportunistic networks.